Overview of the history of cultural development of the Indian community in Ho Chi Minh City, Vietnam - Phuong, Nguyen Minh; Giang, Nguyen Minh; Dinh, Tran Hai (Edelweiss Applied Science and Technology, 2024)
Vietnam and India are two countries that had a very early diplomatic relationship nurtured by the people of two countries over time. Among the factors that create strong bond between Vietnam and India, it is impossible not to mention the presence of Indian community. The Indian community in Ho Chi Minh City is creating the cultural diversity of this land. They have also contributed to cultural exchanges with Vietnamese, attracting investment from India, tightening relations between two countries in the new stage of development. The article uses the theory of cultural exchange and acculturation to study the socio-cultural and economic life of Indians in Ho Chi Minh City in the context of urban culture in the era of globalization. The article is designed with two main contents: First, the historical movements of Indian community in Ho Chi Minh City, Second, the acculturation and cultural exchanges between Vietnamese and Indian community in Ho Chi Minh City. The research results aim to analyze and explain the phenomenon of cultural exchange and acculturation in the fields of economics, religion, and clothing. Thereby, the article contributes to providing documents for cultural preservation, attracting investment, and developing spiritual tourism in Ho Chi Minh City.